Impact of Custom Foot Orthosis on Dynamic Balance in Sports Enthusiasts with Flat Feet - Bahrunnajah, Anastya Yuridha; Fatati, Muhibbah; Anggriani, Atika Febri (Journal of Prosthetics Orthotics and Science Technology, 2024)
Background: Custom foot orthoses (CFOs) have been extensively studied for their effectiveness in redistributing plantar pressure, aligning foot structure, and enhancing stability in individuals with flatfoot (Desmyttere et al., 2019; Xu et al., 2020). Flatfoot, characterized by reduced or absent arches, often leads to overpronation and compromised musculoskeletal alignment, impacting dynamic balance and elevating injury risk during physical activity (Hawke et al., 2015). This study examines the impact of CFOs on dynamic balance specifically in sports-active individuals with flatfoot, where optimal balance is critical due to rapid directional changes and stability demands. By providing customized support, CFOs may serve as a practical intervention to improve stability and support safe sports participation.  Methods: This quantitative, experimental study used a one-group pre-test and post-test design with purposive sampling. Twelve subjects participated, and dynamic balance was measured using the Modified Bass Dynamic Balance Test. Results: Statistical analysis with a paired-sample t-test yielded a p-value of 0.002, indicating a significant positive effect of CFOs on dynamic balance (p < 0.005). Conclusion: The findings indicate a positive effect of CFOs on dynamic balance in flatfoot individuals engaged in sports. It is recommended that individuals with flatfoot, particularly those involved in sports, consider CFOs to improve balance and reduce injury risk. Regular assessments by healthcare professionals may further optimize orthotic benefits for enhanced performance and stability.